Relationship among symptoms, quality of life, and complementary and alternative medicines use among patients undergoing hemodialysis in French-speaking Switzerland - Marie Kemnitz; Matteo Antonini; Philippe Delmas (BMC, 2023)
Abstract Background Chronic renal disease is considered a main public health problem due to its high prevalence in the population. The solution of choice currently available is kidney transplantation but when this option is not available, blood purification treatments, notably haemodialysis (HD), are necessary. The presence of chronic renal disease combined with this demanding medical procedure leads to a hard symptomatology. To face this situation, HD patients often resort to complementary and alternative medicines (CAM) as they perceive that the healthcare professionals aren't paying enough attention to their quality of life. Given this background, we aim to describe the prevalence and the type of the CAM used among HD patients and their possible relations with patients' symptomatology and quality of life. Methods We interviewed 88 patients, undergoing hemodialysis in three hemodialysis centers in French-speaking Switzerland, about the presence of symptoms, their quality of life, and the possible use of CAM. Cluster analysis was used to create patients' profiles about CAM use and regression analysis to explore the links between symptoms' presence, patients' quality of life, and CAM use. Results Our results show a large use of CAM: almost two HD patients out of three uses at least one CAM. Using cluster analysis, we were able to identify five patients' profiles: non-users (37.5% of our sample), users of herbal medicine (20.5%), users of prayer-based practices (18.2%), people mainly using massages (9.1%), and a residual group including the users of other CAMs, with a predominance of meditation (14.8%). As expected, we observe a negative relation between the number of declared symptoms and patients' quality of life. Contrarily, we observe no relation between the use of CAM and the presence of symptoms. Our results show a positive relationship between the use of CAM and patients' overall perception of health as well as the psychological dimension of their quality of life. No relationship is observed with other dimensions of quality of life, notably the physical dimension. Conclusions Our results suggests that CAMs aren't used as a substitute of official medicine but as a parallel support to HD patients' quality of life.